Ethical issues in business : inquiries, cases, and readings - Tittle, Peg, 1957- (2017)
"The long-awaited second edition of Peg Tittle's ambitious business ethics text brings together readings, cases, and the author's own informed opinions on the central ethical issues faced by the business community today. This book examines important contemporary topics such as privacy in IT and whistleblowing, as well as broad questions about the nature of business and the ideal forms of corporate governance. A substantial introduction to ethical theory and thoughtful discussion questions offer guidance to readers unsure how to approach the book's weighty themes. An appendix on the institutions of ethics shows the connection between the philosophical issues at play and the ethics officers, programs, and codes often encountered in the workplace."--
Includes bibliographical references.
Keywords: Business ethics; Business ethics -- Case studies; Business ethics -- Canada; Business ethics; Canada; Case studies